MSCs-Derived Decellularised Matrix: Cellular Responses and Regenerative Dentistry - Suphalak Phothichailert; Shirel Samoun; Benjamin P. Fournier; Juliane Isaac; Sindy Cornelia Nelwan; Thanaphum Osathanon; Nunthawan Nowwarote (International Dental Journal, 2024)
The decellularised extracellular matrix (dECM) of in vitro cell culture is a naturally derived biomaterial formed by the removal of cellular components. The compositions of molecules in the extracellular matrix (ECM) differ depending on various factors, including the culture conditions. Cell-derived ECM provides a 3-dimensional structure that has a complex influence on cell signalling, which in turn affects cell survival and differentiation. This review describes the effects of dECM derived from mesenchymal stem cells (MSCs) on cell responses, including cell migration, cell proliferation, and cell differentiation in vitro. Published articles were searched in the PubMed databases in 2005 to 2022, with assigned keywords (MSCs and decellularisation and cell culture). The 41 articles were reviewed, with the following criteria. (1) ECM was produced exclusively from MSCs; (2) decellularisation processes were performed; and (3) the dECM production was discussed in terms of culture systems and specific supplementations that are suitable for creating the dECM biomaterials. The dECM derived from MSCs supports cell adhesion, enhances cell proliferation, and promotes cell differentiation. Importantly, dECM derived from dental MSCs shows promise in regenerative dentistry applications. Therefore, the literature strongly supports cell-based dECMs as a promising option for innovative tissue engineering approaches for regenerative medicine.